Eudamonia in the theories of Søren Kierkegaard and Gregory of Nyssa - Eliopoulos, Panos (SCHOLE, 2008)
P. Eliopoulos (Tripoli, Greece) compares the attitudes to happiness taken by two Christian philosophers, separated by a very wide margin of space and time, Gregory of Nyssa and Søren Kierkegaard.